Network-based modelling and active control for offshore steel jacket platform with TMD mechanisms - Zhang, Bao-Lin; Han, Qing-Long (Journal of sound and vibration, 2014)
The network-based modelling and active control for an offshore steel jacket platform with an active tuned mass damper mechanism is investigated. A network-based dynamic model of the offshore platform is first established. A network-based state feedback control scheme is developed. Under this scheme, the corresponding closed-loop system is modelled by a system with an artificial interval time-varying delay. Then, a delay-dependent stability criterion for the corresponding closed-loop system is derived. Based on this stability criterion, a sufficient condition on the existence of the network-based controller is obtained. It is found through simulation results that (i) both the oscillation amplitudes of the offshore platform and the required control force under the network-based state feedback controller are smaller than those under the nonlinear controller and the dynamic output feedback controller; (ii) the oscillation amplitudes of the offshore steel jacket platform under the network-based feedback controller are almost the same as the ones under the integral sliding mode controller, while the required control force by the former is smaller than the one by the latter.